THE INFLUENCE OF ORGANIZATIONAL CULTURE, WORK ENVIRONMENT, AND ORGANIZATIONAL COMMITMENT ON EMPLOYEES JOB SATISFACTION AT PT. XYZ - ARIFIN, LENNY NOVIANA; FARIDA, IDA (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
This study aims to determine the influence of organizational culture, work environment, and organizational commitment on employees job satisfaction at PT. XYZ. This research was conducted at PT. XYZ with a population of 76 employees. The saturated sample technique was used to sample 76 employees. Primary data collection techniques were collected by disseminating research questionnaires with Likert scale. The analysis technique in this study uses multiple linear regression analysis. Based on the results of data analysis, the hypothesis test in this study shows that organizational culture affects job satisfaction, work environment affects job satisfaction, and organizational commitment does not affect job satisfaction.